Interrogating the Function of Metazoan Histones using Engineered Gene Clusters. - McKay, D.J.; Klusza, S.; Penke, T.J.; Meers, M.P.; Curry, K.P.; McDaniel, S.L.; Malek, P.Y.; Cooper, S.W.; Tatomer, D.C.; Lieb, J.D.; Strahl, B.D.; Duronio, R.J.; et al. (Developmental Cell, 2015)
Histones and their posttranslational modifications influence the regulation of many DNA-dependent processes. Although an essential role for histone-modifying enzymes in these processes is well established, defining the specific contribution of individual histone residues remains a challenge because many histone-modifying enzymes have nonhistone targets. This challenge is exacerbated by the paucity of suitable approaches to genetically engineer histone genes in metazoans. Here, we describe a platform in Drosophila for generating and analyzing any desired histone genotype, and we use it to test the in vivo function of three histone residues. We demonstrate that H4K20 is neither essential for DNA replication nor for completion of development, unlike inferences drawn from analyses of H4K20 methyltransferases. We also show that H3K36 is required for viability and H3K27 is essential for maintenance of cellular identity but not for gene activation. These findings highlight the power of engineering histones to interrogate genome structure and function in animals.